Design modification of iron ore bearing transfer chute using discrete element method. Issue 9 (5th April 2021) - Basu, Saprativ; Chakrabarty, Arijit; Nag, Samik; Behera, Kishore; Bandyopadhyay, Brati; Grima, Andrew Phillip; Ghosh, Probal
Abstract : Purpose: The dryer feed chute of the pellet plant plays an important role in the pelletizing process. The chute discharges sticky and moist iron ore fines (<1 mm) to the inline rotary dryer for further processing. Since the inception of the installation of the dryer feed chute, the poor flowability of the feed materials has caused severe problems such as blockages and excessive wear of chute liners. This leads to high maintenance costs and reduced lifetime of the liner materials. Constant housekeeping is needed for maintaining the chute and reliable operation. The purpose of this study is to redesign the dryer feed chute to overcome the above challenges. Design/methodology/approach: The discrete element method (DEM) has been used to model the flow of cohesive materials through the transfer chute. Physical experiments have been performed to understand the most severe flow conditions. A DEM material model is also developed for replicating the worst-case material condition. After identifying the key problem areas, concept designs were proposed and simulated to assess the design improvements to increase the reliability of chute operation. Findings: Flow simulations correlated well with the existing flow behavior of the iron ore fines inside the chute. The location of the problematic areas has been validated with that of the previously installed chute. Subsequently, design modifications have been proposed. This includes modification of deflector plate and change in slope and cross-section of the chute. DEM simulations and analysis were conducted after incorporating these design changes. A comparison in the average velocity of particle and force on chute wall shows a significant improvement using the proposed design. Originality/value: Method to calibrate DEM material model was found to provide accurate prediction and modeling of the flow behavior of bulk material through the real transfer chute. DEM provided greater insight into the performance of the chute especially modeling cohesive materials. DEM is a valuable design tool to assist chute designers troubleshoot and verify chute designs. DEM provides a greater ability to model and assess chute wear. This technique can help in achieving a scientific understanding of the flow properties of bulk solids through transfer chute, hence eliminate challenges, ensuring reliable, uninterrupted and profitable plant operation. This paper strongly advocates the use of calibrated DEM methodology in designing bulk material handling equipment.